Efficacy of Video Electroencephalography in the Classification of Epilepsy (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2024)
Background:Epilepsy is common neurological disease that affect people of all ages, genders, ethnic backgrounds, and cultures, regardless of their geographical location. It is also considered the second cause of neurological diseases in the world.This study aims to study the usefulness of video electroencephalography recording in the classification of patients with epilepsy according to ictal and interictal findings supplemented with clinical history and detailed description of the event.Materials and methods:The study was a cross sectional study conducted in the period between September 2022 until April 2023 conducted in neurology ward/ video EEG room in Al-Sadeq teaching hospital in Al-Hillah city. It’s included 47 patients. Patients are recruited from video electroencephalographic room in neurology ward after being diagnosed to have epilepsy by experienced neurologist. The diagnosis of epilepsy by the neurologist depends on clinical history including detailed history of the ictal event by the patient, his family supported by analysis of video recording of the ictal event, imaging studies if needed and finally by ordinary electroencephalogram examination done at the hospital for 20-30 minutes. The diagnosis and classification were based on the latest reports of international league against epilepsy.Results:The study results showed the percent of patients who had interictal discharges through electroencephalography recording 91.48%, and 10.5% of patients had ictal state throughout recording. The classification of seizure subtype according international league against epilepsy-2017 was 11 patient classified as focal onset seizure and 36 of them had generalized onset. Also video electroencephalogram results in altering the initial classification of epilepsy in 57.45% of patients.Conclusion:Video electroencephalography is a powerful tool in the classification of epileptic syndromes.